INDEKS KEANEKARAGAMAN BAKTERI BACILLUS SP. DARI TANAH KEBUN RAYA LIWA - Kusuma Handayani; Vidia Royanti; Chistina Nugroho Ekowati (UIN Sunan Gunung Djati Bandung, 2023)
Bacillus sp is a bacterium that is commonly found in soil, water, air and plant debris, has the ability to produce enzymes and degrade natural substrates so that it contributes to the nutrient cycle. The Kebun Raya Liwa area is located at an altitude between 890 to 948 meters above sea level where at this altitude is included in a hilly area. With varying topographic conditions so that it has different soil conditions. This can trigger the diversity of Bacillus sp. The purpose of this study was to determine the diversity index of Bacillus sp in the Liwa Botanical Gardens soil. This research was conducted at the microbiology laboratory of the Mathematics and Natural Sciences faculty, Lampung University. The method used is sampling using five different types of soil, namely litter soil, biopori soil, arase sloping soil, ordinary soil, and ordinary arase soil. The isolation technique uses the pour plate method with multilevel dilutions. Calculation of diversity using a calculation method that refers to the calculation of Shanon Wiener. The results of this study obtained the highest diversity of Bacillus sp in litter soil with a total index of 2.488464 indicating a moderate level of diversity while the lowest total value was obtained in biopore soil with a value of 1.351604 indicating a moderate level of diversity. The high and low diversity of Bacillus sp bacteria can be caused by environmental conditions. In this study, the dominant morphology of Bacillus sp is circular colony shape.